The hypolipidemic effect of MI-883, the combined CAR agonist/ PXR antagonist, in diet-induced hypercholesterolemia model - Dusek, Jan; Mejdrová, Ivana; Dohnalová, Klára; Smutny, Tomas; Chalupsky, Karel; Krutakova, Maria; Skoda, Josef; Rashidian, Azam; Pavkova, Ivona; Škach, Kryštof; Hricová, Jana; Chocholouskova, Michaela; et al. (Nature communications, 2025)
Constitutive androstane receptor (CAR) and pregnane X receptor (PXR) are closely related nuclear receptors with overlapping regulatory functions in xenobiotic clearance but distinct roles in endobiotic metabolism. Car activation has been demonstrated to ameliorate hypercholesterolemia by regulating cholesterol metabolism and bile acid elimination, whereas PXR activation is associated with hypercholesterolemia and liver steatosis. Here we show a human CAR agonist/PXR antagonist, MI-883, which effectively regulates genes related to xenobiotic metabolism and cholesterol/bile acid homeostasis by leveraging CAR and PXR interactions in gene regulation. Through comprehensive analyses utilizing lipidomics, bile acid metabolomics, and transcriptomics in humanized PXR-CAR-CYP3A4/3A7 mice fed high-fat and high-cholesterol diets, we demonstrate that MI-883 significantly reduces plasma cholesterol levels and enhances fecal bile acid excretion. This work paves the way for the development of ligands targeting multiple xenobiotic nuclear receptors. Such ligands hold the potential for precise modulation of liver metabolism, offering new therapeutic strategies for metabolic disorders.
Keywords: Cholesterol; lidé; cholesterol; Cytochrome P-450 CYP3A; pregnanový X receptor; Pregnane X Receptor; Bile Acids and Salts; myši; dieta s vysokým obsahem tuků; Humans; Mice; Receptors, Cytoplasmic and Nuclear; hypercholesterolemie; Disease Models, Animal; cytochrom P-450 CYP3A; mužské pohlaví; Hypercholesterolemia; zvířata; hypolipidemika; játra; receptory cytoplazmatické a nukleární; Mice, Inbred C57BL; Liver; Hypolipidemic Agents; Animals; Male; konstitutivní androstanový receptor; modely nemocí na zvířatech; žlučové kyseliny a soli; Diet, High-Fat; myši inbrední C57BL; Constitutive Androstane Receptor